Estudos (inter) culturais em cadernos de língua inglesa da rede pública do estado de São Paulo - Kovalek, Olena (2013)
We intend, from this research of documental and interpretativist character, to investigate how the cultural contents linked to the teaching and learning of English language are approached, considering the São Paulo State educational material distributed to public high schools. To carry out this work, we consider that, as much as the curricular proposal of São Paulo State presented as one of its most important features the curriculum as a cultural space , possibly the cultural contents also might appear on the material distributed to the students and for the teachers. Thus, we analyzed on the teacher material the proceedings for carrying out the contents and the activities. On students material, we analyzed the activities divided on learning situations . We focused the cultural contents culture definitions proposed by Thompson (2002), stereotypes, social representations, cultural identities and alterity plans proposed by Todorov (1995) on the intercultural processes of teaching and learning, as such on the designations of English language around the world. Besides that, before the analysis, we made the description of cultural contents present on the Current curricular proposal of São Paulo State , and we propose definition for didactic materials, textbooks and Cadernos to comprehend the choice of the term Cadernos by its organizers. Throughout the analysis we propose changes, when necessary, on the proceedings and on the Cadernos activities, in order to approach the cultural contents in an explicit way on the classes, and to reflect about them on a critical and conscious way (BYRAM; GRIBKOVA; STARKEY, 2002). With the activities realized, we had conditions to group them as answers to our research questions. In a general way, we can assure that the cultural contents appear on the Cadernos either on the proceedings and on the activities, but, most of the times, on an implicit manner; we noticed the concern in using important concepts on the proceedings and the orientations of the teachers Cadernos (interculturality, cultural diversity, English speaking countries, and others), but these concepts were scarcely presented to the teachers, and, when they were explained, we noticed the absence of clear explanations of the concepts as much as its contextualization, in order that the teacher may comprehend and work with them on his classes. As theoretical foundation, we based the research on some authors, as Almeida Filho (2002; 2011); Barbosa (2007; 2008; 2009); Byram et al.(2002); Hall (2005); Hurst (2006); Kramsch (1993; 1998; 2009), Viana (2003), among others.